Determinants of buildup of the toxic dopamine metabolite DOPAL in Parkinson's disease. (22nd July 2013) - Goldstein, David S.; Sullivan, Patti; Holmes, Courtney; Miller, Gary W.; Alter, Shawn; Strong, Randy; Mash, Deborah C.; Kopin, Irwin J.; Sharabi, Yehonatan
Abstract: Intra‐neuronal metabolism of dopamine (DA) begins with production of 3, 4‐dihydroxyphenylacetaldehyde (DOPAL), which is toxic. According to the 'catecholaldehyde hypothesis, ' DOPAL destroys nigrostriatal DA terminals and contributes to the profound putamen DA deficiency that characterizes Parkinson's disease (PD). We tested the feasibility of using post‐mortem patterns of putamen tissue catechols to examine contributions of altered activities of the type 2 vesicular monoamine transporter (VMAT2) and aldehyde dehydrogenase (ALDH) to the increased DOPAL levels found in PD. Theoretically, the DA : DOPA concentration ratio indicates vesicular uptake, and the 3, 4‐dihydroxyphenylacetic acid : DOPAL ratio indicates ALDH activity. We validated these indices in transgenic mice with very low vesicular uptake (VMAT2‐Lo) or with knockouts of the genes encoding ALDH1A1 and ALDH2 (ALDH1A1, 2 KO), applied these indices in PD putamen, and estimated the percent decreases in vesicular uptake and ALDH activity in PD. VMAT2‐Lo mice had markedly decreased DA:DOPA (50 vs. 1377, p < 0.0001), and ALDH1A1, 2 KO mice had decreased 3, 4‐dihydroxyphenylacetic acid:DOPAL (1.0 vs. 11.2, p < 0.0001). In PD putamen, vesicular uptake was estimated to be decreased by 89% and ALDH activity by 70%. Elevated DOPAL levels in PD putamen reflect a combination of decreased vesicular uptake of cytosolic DA and decreased DOPAL detoxification by ALDH. According to the 'catecholaldehyde hypothesis, ' the toxic dopamine metabolite DOPAL contributes to loss of striatal dopaminergic innervation in Parkinson's disease. Here we provide post‐mortem neurochemical evidence that in Parkinson's disease patients, putamen DOPAL buildup reflects decreased vesicular sequestration of cytosolic dopamine and decreased DOPAL metabolism by aldehyde dehydrogenase. The results fit with an intra‐neuronal autotoxic mechanism of Parkinson's disease. Abstract : According to the 'catecholaldehyde hypothesis, ' the toxic dopamine metabolite DOPAL contributes to loss of striatal dopaminergic innervation in Parkinson's disease. Here we provide post‐mortem neurochemical evidence that in Parkinson's disease patients, putamen DOPAL buildup reflects decreased vesicular sequestration of cytosolic dopamine and decreased DOPAL metabolism by aldehyde dehydrogenase. The results fit with an intra‐neuronal autotoxic mechanism of Parkinson's disease.